2024
DOI: 10.3390/cancers16010224
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β/Smad Signaling Inhibits Melanoma Cancer Stem Cell Self-Renewal, Tumor Formation and Metastasis

Julien Boudreault,
Ni Wang,
Mostafa Ghozlan
et al.

Abstract: The secreted protein transforming growth factor-beta (TGFβ) plays essential roles, ranging from cell growth regulation and cell differentiation in both normal and cancer cells. In melanoma, TGFβ acts as a potent tumor suppressor in melanoma by blocking cell cycle progression and inducing apoptosis. In the present study, we found TGFβ to regulate cancer stemness in melanoma through the Smad signaling pathway. We discovered that TGFβ/Smad signaling inhibits melanosphere formation in multiple melanoma cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 69 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…MEN1 patients can develop malignancies other than classical endocrine tumors, including skin tumors [ 29 ]. Previous work from our laboratory and others showed that the TGFβ signaling pathway acts as a potent tumor suppressor in melanoma [ 12 , 13 , 14 , 15 ]. Thus, we investigated whether MEN1 could relay some of the TGFβ tumor-suppressive response in melanoma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MEN1 patients can develop malignancies other than classical endocrine tumors, including skin tumors [ 29 ]. Previous work from our laboratory and others showed that the TGFβ signaling pathway acts as a potent tumor suppressor in melanoma [ 12 , 13 , 14 , 15 ]. Thus, we investigated whether MEN1 could relay some of the TGFβ tumor-suppressive response in melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…The TGFβ/Smad signaling pathway exerts potent tumor-suppressive effects on melanoma [ 15 ]. We thus investigated the role and contribution of MEN1 downstream of TGFβ-mediated growth inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that TGF-β acts as a potent suppressor of tumour development, migration, and metastasis. Additionally, it has been shown that there is potential in the use of agents that stimulate or mimic TGF-β as new methods to fight melanoma [159].…”
Section: Perspectives and Modern Therapeutic Strategies Targeting Csc...mentioning
confidence: 99%
“…Also, for an efficacious therapy, all CSCs should be precisely eradicated to minimise risk of recurrence. In the past few years, a global effort has been made to design innovative therapeutic strategies against CSCs [10,[150][151][152][153][154][155][156][157][158][159]. The results seem to be promising to improve long-term health outcomes; however, the biology of CSCs and their susceptibility to various types of therapy depend on the model on which the research was carried out.…”
Section: Perspectives and Modern Therapeutic Strategies Targeting Csc...mentioning
confidence: 99%